Addressing Language Errors in L2 Students' Writing: Can Corpora Help? - Baghestani, Shireen (2011)
A Master of Arts thesis in Teaching English to Speakers of Other Languages (TESOL) by Shireen Palmer Baghestani entitled, "Addressing Language Errors in L2 Students' Writing: Can Corpora Help," submitted in June 2011. Available are both hard and soft copies of the thesis.